Movement Analysis of Momtong Dollyo and Eolgol Dollyo Chagi Kicks in Kyorugi Athletes at Orion Taekwondo Dojang, Kepahiang, Bengkulu - Arie Asnaldi; Selvi Zalehah; Weny Sasmitha; Suwirman Suwirman (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This study aims to analyze the movement techniques of momtong dollyo and eolgol dollyo chagi kicks in kyorugi athletes at the Orion Taekwondo dojang, which, based on initial observations, still show weak mastery of basic techniques. The approach used is descriptive with a case study method, involving 14 kyorugi athletes selected purposively. Technique assessment was conducted using an assessment rubric and evaluated by judgment through observation of four technical aspects: initial stance, execution, final stance, and dominant kicks. Data analysis was carried out using a quantitative descriptive model with a percentage formula. The research results showed that 65.47% of athletes were classified as athletes who frequently use the eolgol dollyo chagi kick, while 96.42% of athletes mostly used the momtong dollyo chagi kick. It can be concluded that the momtong dollyo chagi kick is more often used in competitions because it is easier to perform compared to the eolgol dollyo chagi kick, with the tendency that the kicks used by athletes aim to score as many points as possible and win the match.